Clinical benefits of a modified Cryopiece system for cryopreservation of rare ejaculated and testicular spermatozoa for ICSI - Wei Chen; Chuan Huang; Peng Li; Feng Liu; Jian Sun; Zi-Jue Zhu; Jing Zhai; Yuan Xu; Yan Hong; Jian-Lin Hu; Yun-Peng Peng; Zhen-Bo Zhang; et al. (Asian Journal of Andrology, 2022)
Cryopreservation of rare testicular-retrieved spermatozoa for intracytoplasmic sperm injection (ICSI) in patients with severe oligozoospermia and azoospermia remains a major challenge in clinical practice. This study evaluated the Cryopiece system as a potential technique to cryopreserve rare human spermatozoa for ICSI. Small numbers of ejaculated (24 patients) and testicular (13 patients) spermatozoa were cryopreserved using the Cryopiece system. The total number of recovered spermatozoa and motility were assessed after thawing. Thirty-seven couples underwent ICSI using spermatozoa cryopreserved by the Cryopiece system, and ICSI outcomes (rates of fertilization, embryo cleavage, and clinical pregnancy) were evaluated. The average sperm post-thaw retrieval rate was 79.1%, and motility was 29.7%. Ejaculated spermatozoa had a higher post-thaw motility (32.5%) than testicular spermatozoa (21.8%; P = 0.005). ICSI achieved a fertilization rate of 61.9%, embryo cleavage rate of 84.6%, and clinical pregnancy rate of 43.3%. The ICSI outcomes in the ejaculated and testicular frozen-thawed spermatozoa were similar. Assisted oocyte activation (AOA) after ICSI with motile (72.1%) or immotile (71.9%) spermatozoa resulted in a significantly higher fertilization rate than that when using motile spermatozoa without AOA (52.0%; P = 0.005). However, AOA did not enhance the clinical pregnancy rate (55.6% or 40.0% vs 35.3%; P = 0.703). The Cryopiece system is simple and useful for the cryopreservation of small numbers of ejaculated or testicular spermatozoa for ICSI in patients with severe oligozoospermia or nonobstructive azoospermia.